DAYA HAMBAT EKSTRAK RIMPANG TEMU PUTIH (Curcuma zedoaria) TERHADAP Streptococcus mutans DAN Staphylococcus aureus - Busman, Edrizal, Siska Desri Wirahmi (Menara Ilmu, 2019)
Oral cavity is a place of entry of various kinds of bacteria into the body. The main causes of dental caries are Streptococcus mutans and Staphylococcus aureus. White gathering has benefits for the body including toothache medicine, eliminating bad breath and sore throat. The purpose of this study was to determine the inhibitory effect of rhizome extract of white intersection (Curcuma zedoaria) against Streptococcus mutans and Staphylococcus aureus. The type of research used is laboratory experimental, the research sample is bacterium Streptococcus mutans and Staphylococcus aureus obtained from laboratory of Microbiology University of Indonesia. This study used concentrations of 20%, 40%, 60% and 80% as well as positive control using amoxicillin and negative control using DMSO. Data analysis using One Way Anova test. The results obtained sig value = 0.000 <0.05. From this research, it was found that white rhizome extract (Curcuma zedoaria) can inhibit the growth of Streptococcus mutans and Staphylococcus aureus bacteria in the extract concentrations of 20%, 40%, 60% and 80%. The conclusion of this research is the inhibition of white rhizome extract extract (Curcuma zedoaria) against Streptococcus mutans with 40% concentration of 16.96 mm and in Staphylococcus aureus bacteria with 80% concentration of 23.98 mm. Key Word : Ekstrak rimpang temu putih (Curcuma zedoaria), Staphylococcus aureus dan Streptococcus mutans